(x-4)+5(x-3)=2(3x-5)

Simple and best practice solution for (x-4)+5(x-3)=2(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-4)+5(x-3)=2(3x-5) equation:


Simplifying
(x + -4) + 5(x + -3) = 2(3x + -5)

Reorder the terms:
(-4 + x) + 5(x + -3) = 2(3x + -5)

Remove parenthesis around (-4 + x)
-4 + x + 5(x + -3) = 2(3x + -5)

Reorder the terms:
-4 + x + 5(-3 + x) = 2(3x + -5)
-4 + x + (-3 * 5 + x * 5) = 2(3x + -5)
-4 + x + (-15 + 5x) = 2(3x + -5)

Reorder the terms:
-4 + -15 + x + 5x = 2(3x + -5)

Combine like terms: -4 + -15 = -19
-19 + x + 5x = 2(3x + -5)

Combine like terms: x + 5x = 6x
-19 + 6x = 2(3x + -5)

Reorder the terms:
-19 + 6x = 2(-5 + 3x)
-19 + 6x = (-5 * 2 + 3x * 2)
-19 + 6x = (-10 + 6x)

Add '-6x' to each side of the equation.
-19 + 6x + -6x = -10 + 6x + -6x

Combine like terms: 6x + -6x = 0
-19 + 0 = -10 + 6x + -6x
-19 = -10 + 6x + -6x

Combine like terms: 6x + -6x = 0
-19 = -10 + 0
-19 = -10

Solving
-19 = -10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2x+6=42 | | 7y-9=3(y+5) | | 6(7-8x)=186 | | (2x+3)(5x-1)=0 | | 5(t-2)=t+10 | | 9p+6=3(p+8) | | 4b=6b+-19 | | 4(x+2)=3x+11 | | 3x^2+10+8=0 | | 3p^2-28=27p | | 4(n-1)=n+14 | | 4y^3-3=-12y^2+y | | 10+2z=20 | | -6+x=-10 | | 12t-1=14t-5 | | 8k+10=13k-5 | | 3v^2-7v-20= | | 3a=5a-18 | | 6(x+2)=3(x-5) | | 5x+37=14x-62 | | x^2+5x+18=9 | | 4x+7=x+16 | | 15r+22=97 | | 3(x-4)+5(x+3)=2(3x-5)-6 | | 6(2x-5)=42 | | -4x+2(4-3x)=8-10x | | 9x-21=3+3 | | 3r+12=r+34 | | 4p+8=10p+2 | | -x^2+50x-350=0 | | 8t^2-6t=9 | | x^5-x^4+9x^3-9x^2=0 |

Equations solver categories